Composite resin disc as well as preparation method and application thereof
By combining barium silanized glass powder and modified fumed silica filler with a resin matrix, and using a three-stage dispersion and gradient curing process, a high-strength, low-shrinkage composite resin disc was prepared. This solved the material defects of zirconia ceramics and light-cured composite resins, and met the needs of immediate restoration and long-term durability in dental restoration.
Patent Information
- Application Number
- CN202511622787.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-07
- Publication Date
- 2026-02-06
AI Technical Summary
Existing zirconia ceramic materials are brittle and prone to breakage, and their high hardness leads to wear on opposing teeth. Light-cured composite resins have insufficient mechanical properties, significant polymerization shrinkage, low processing efficiency, and poor biostability, which cannot meet the clinical needs for immediate restoration and long-term durability.
A composite resin disk was prepared by using a combination of barium silanized glass powder and modified fumed silica as fillers, in conjunction with a resin matrix and functional additives, through a three-stage dispersion and gradient curing process. This improved the material's flexural strength, elastic modulus, and reduced polymerization shrinkage.
The composite resin disc achieved a flexural strength of over 310 MPa, an elastic modulus of 15 GPa, and near-zero shrinkage, breaking through the ceiling of existing material performance and meeting the clinical needs for immediate repair and long-term durability.
Smart Images

Figure CN121465894A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of dental restorative materials technology, and in particular to a composite resin disc, its preparation method, and its application. Background Technology
[0002] With the development of digital dental restoration technology, CAD / CAM systems are increasingly widely used in the field of permanent denture restoration. Currently, the most commonly used restorative materials in clinical practice mainly include two categories: zirconia ceramics and light-cured composite resins.
[0003] While all-ceramic materials such as zirconia possess excellent mechanical strength (flexural strength 600-1100 MPa), their inherent brittleness makes them prone to marginal chipping (clinically reported chipping rate of approximately 8-12%), and their excessively high hardness (1200-1400 HV) can cause abnormal wear on opposing teeth (up to 40-60 μm of wear per year). More importantly, ceramic restorations require high-temperature sintering and multiple processing steps, with the entire preparation cycle taking 3-5 working days, which cannot meet the clinical demand for immediate restoration.
[0004] The photocurable composite resin mainly uses Bis-GMA resin matrix and silicate filler system, which has the following problems: (1) Insufficient mechanical properties: the flexural strength is generally lower than 200 MPa; (2) Significant polymerization shrinkage: the volume shrinkage rate is 2-5%, which leads to micro-leakage at the edge of the repair; (3) Low processing efficiency: traditional photocuring requires layer processing (each layer ≤2 mm), and the total curing time exceeds 30 minutes; (4) Poor biological stability: the water absorption rate >3wt% affects the dimensional stability, and the surface is prone to forming bacterial biofilm.
[0005] In actual clinical practice, patients want repair treatment to be both fast and long-lasting. On the one hand, they hope that the repair can be completed in a single visit, and on the other hand, they hope that the five-year durability success rate can reach 90%. However, current repair treatments require 2-3 visits, and the five-year durability success rate is only 80-85%.
[0006] Given the problems with existing technologies, it is essential to develop a new type of repair material.
[0007] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of patent protection of this application. Summary of the Invention
[0008] This application provides a composite resin disk, its preparation method, and its application to solve or alleviate one or more of the technical problems mentioned above.
[0009] The first aspect of this application provides a composite resin disc, wherein the raw materials of the composite resin disc include: a resin matrix with a mass percentage of 10-30%, 70-90% filler, and the balance being functional additives. The filler is a combination of barium silanide glass powder and modified fumed silica; The resin matrix comprises 5-10% by weight of bisphenol A-glycidyl methacrylate, 2-10% of urethane dimethacrylate, 1-10% of triethylene dimethacrylate, 0.1-1% of hydroxyethyl methacrylate, 0.1-1% of methyl methacrylate, and 0.1-1% of methacrylic acid.
[0010] Optionally, the mass ratio of the barium silanide glass powder to the modified fumed silica is (10-20):1.
[0011] Optionally, the average particle size of the barium silanide glass powder is 0.7-1 μm.
[0012] Optionally, the modified fumed silica has an average particle size of 5-20 nm.
[0013] Optionally, the preparation method of the filler includes: adding barium glass powder and fumed silica to the modified solution, ultrasonically dispersing at 50-70℃ for 30-60 min, and drying to obtain the filler.
[0014] Optionally, the mass ratio of the modified solution to barium glass powder is (1.5-5):1.
[0015] Optionally, the mass ratio of the modified solution to fumed silica is (0.5-3.5):1; Optionally, the drying process includes: first drying at 55-65℃ for 1-3 hours, then drying at 70-80℃ for 1-3 hours, and then drying at 85-95℃ for 7-9 hours.
[0016] Optionally, the method for preparing the modified solution includes: mixing ethanol, water and a silane coupling agent to obtain the modified solution.
[0017] Optionally, the mass ratio of the ethanol, water and silane coupling agent is (5-8.5):(2-5.5):(0.5-1.5).
[0018] Optionally, the mixing rate is 400-600 rpm and the mixing time is 0.5-2 h.
[0019] Optionally, the functional additives include any one or a combination of at least two of antioxidants, bactericides, emulsifiers, or pigments.
[0020] Optionally, the antioxidant includes any one or a combination of at least two of antioxidants 1010, 1076, 264, or 168.
[0021] Optionally, the bactericide includes nano-silver.
[0022] Optionally, the emulsifier includes any one or a combination of at least two of octylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether, or higher carbon fatty alcohol polyoxyethylene ether.
[0023] Optionally, the pigment includes any one or a combination of at least two of iron oxide red, iron oxide yellow, or iron oxide black.
[0024] Optionally, the flexural strength of the composite resin disk is 300-350 MPa.
[0025] Optionally, the elastic modulus of the composite disk is 14-20 GPa.
[0026] Optionally, the composite disk has a Vickers hardness of 75-85 HV 0.2.
[0027] Optionally, the polymerization shrinkage rate of the composite disk is 0.
[0028] Secondly, embodiments of this application provide a method for preparing the composite disk described in the first aspect, the method comprising: (1) The resin matrix, barium silanide glass powder, fumed silica and functional additives are mixed, dispersed and prepolymerized to obtain a mixture; (2) Degas the mixture obtained in step (1) and then mold and cure it to obtain a composite resin disc.
[0029] In this application, the preparation method of the composite resin disk is simple, the raw materials are readily available, and it is convenient for large-scale production and application.
[0030] Optionally, the mixing and dispersion in step (1) includes three-stage dispersion, wherein the first stage is premixing for 60-120 min at a temperature of 45-55℃ and a stirring rate of 2000-3000 rpm; the second stage is high-shear mixing for 30-90 min at a temperature of 55-65℃ and a stirring rate of 4000-6000 rpm; and the third stage is ultrasonic mixing for 10-20 min at a frequency of 30-50 kHz and a stirring rate of 1000-2000 rpm. Optionally, the prepolymerization in step (1) includes a three-stage gradient heating, wherein: the temperature of the first stage is 50-70℃ and held for 20-40 min; the temperature of the second stage is 80-100℃ and held for 10-30 min; and the temperature of the third stage is 110-130℃ and held for 5-15 min.
[0031] Optionally, the prepolymerization in step (1) is carried out under stirring conditions, wherein the stirring rate is 200-1000 r / min.
[0032] In this application, a three-stage gradient heating method is employed. The first step, at a low temperature, triggers homolytic cracking of the initiator to generate a small amount of free radicals, initiating an initial reaction that reduces monomer concentration and weakens the "auto-accelerated reaction" peak. The second step, at a medium temperature, promotes chain initiation and chain growth, increasing the system viscosity through chain extension reactions while controlling molecular weight distribution. The third step involves appropriate heating to further increase monomer conversion. The purpose of prepolymerization is to reduce monomer concentration and increase viscosity, while also reducing localized stress during subsequent curing. The significance of the stepped heating is that, while achieving the desired effect, it prevents abnormal problems such as uneven molecular weight distribution, excessive heat release in a short time, microbubbles generated by solvent evaporation, and uncontrollable reaction rates caused by the "auto-accelerated reaction of free radicals" through a gradual, step-by-step reaction.
[0033] Optionally, the pressure for molding and curing in step (2) is 100-300 MPa.
[0034] Optionally, the molding curing in step (2) includes curing at 110-180℃ for 1-3 h and then curing at 70-80℃ for 8-12 h.
[0035] Optionally, the degassing in step (2) is completed using a vacuum device combined with instantaneous pressure relief technology.
[0036] Thirdly, embodiments of this application provide an application of the composite resin disc described in the first aspect in denture restoration.
[0037] The embodiments of this application employing the above-described technical solution may have the following advantages: This application utilizes a resin and ceramic synergistic reinforcement system combined with a gradient curing process to achieve a composite resin disc with a flexural strength of over 310 MPa, an elastic modulus of 15 GPa, and near-zero shrinkage, breaking through the ceiling of existing material performance. Attached Figure Description
[0038] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the various drawings denote the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings depict only some embodiments disclosed in this application and should not be construed as limiting the scope of this application.
[0039] Figure 1 This is a schematic diagram of the structure of the composite resin disk provided in the embodiments of this application.
[0040] Figure 2 This is a schematic diagram of the vacuum device used in the fabrication of the composite disk in this application. Detailed Implementation
[0041] The embodiments of this application are described in detail below, examples of which are illustrated in the accompanying drawings. In the drawings, for clarity, the dimensions of layers, regions, and elements, as well as their relative dimensions, may be exaggerated. Throughout, the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other.
[0042] It should be understood that when an element or layer is referred to as "on," "adjacent to," "connected to," or "coupled to" other elements or layers, it may be directly on, adjacent to, connected to, or coupled to other elements or layers, or there may be intervening elements or layers. Conversely, when an element is referred to as "directly on," "directly adjacent to," "directly connected to," or "directly coupled to" other elements or layers, there are no intervening elements or layers. It should be understood that although the terms first, second, third, etc., may be used to describe various elements, components, areas, layers, and / or portions, these elements, components, areas, layers, and / or portions should not be limited by these terms. These terms are only used to distinguish one element, component, area, layer, or portion from another element, component, area, layer, or portion. Therefore, without departing from the teachings of this application, the first element, component, area, layer, or portion discussed below may be referred to as a second element, component, area, layer, or portion. And the discussion of a second element, component, area, layer, or portion does not imply that the first element, component, area, layer, or portion necessarily exists in this application.
[0043] In this application, unless otherwise expressly specified and limited, the terms "installation," "connection," "joining," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components, unless otherwise expressly limited. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.
[0044] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0045] In this application, when numerical intervals (i.e., numerical ranges) are involved, unless otherwise specified, the distribution of selectable numerical values within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, etc.
[0046] This application provides a composite resin disk, its preparation method, and its application technology. Details are provided below.
[0047] Exemplary embodiments according to this application will now be described in more detail with reference to the accompanying drawings. It should be understood that these exemplary embodiments may be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein.
[0048] This application provides a composite resin disc, the raw materials of which include: a resin matrix with a mass percentage of 10-30% (exemplary, mass percentages of 10%, 15%, 20%, 25%, 30%, etc.), 70-90% (exemplary, mass percentages of 70%, 75%, 80%, 85%, 90%, etc.), and the balance being functional additives. The resin matrix comprises 5-10% (e.g., 5%, 6%, 7%, 8%, 9%, 10%) of bisphenol A-glycidyl methacrylate, 2-10% (e.g., 2%, 4%, 6%, 8%, 10%) of urethane dimethacrylate, 1-10% (e.g., 1%, 3%, 5%, 7%, 10%) of triethylene glycol dimethacrylate, 0.1-1% (e.g., 0.1%, 0.3%, 0.5%, 0.8%, 1%) of hydroxyethyl methacrylate, 0.1-1% (e.g., 0.1%, 0.3%, 0.5%, 0.8%, 1%) of methyl methacrylate, and 0.1-1% (e.g., 0.1%, 0.3%, 0.5%, 0.8%, 1%) of methacrylic acid.
[0049] In this application, the composite resin disc, through the combined action of the resin matrix, a specific filler combination, and functional additives, achieves a composite resin disc with strong flexural strength, elastic modulus, Vickers hardness, and a shrinkage rate of 0.
[0050] In this application, the resin matrix serves as the continuous phase and load-bearing matrix of the composite material. Bisphenol A-glycidyl methacrylate (Bis-GMA) provides rigidity and strength, but has a high viscosity. UDMA (urethane dimethacrylate) reinforces and toughens the resin material, with a moderate viscosity. TEGDMA (triethylene glycol dimethacrylate) acts as a diluent to reduce viscosity and improve processability. HEMA (hydroxyethyl methacrylate) is a functional monomer that retains active hydroxyl groups after the reaction, increasing adhesion. MAA (methyl methacrylate) acts as a solvent. The addition of linear components to the methacrylic acid (MMA) resin network structure increases toughness and elasticity. The three-dimensional cross-linked network formed by the resin matrix during curing determines the material's basic mechanical properties, curing shrinkage, and biocompatibility.
[0051] In this application, nano-silica improves mechanical strength: nanoparticles are uniformly dispersed in the resin matrix, effectively transferring and dispersing stress, and improving the flexural and compressive strength of the material; nano-silica enhances wear resistance: high-hardness nanoparticles are dispersed in the gaps between polymer molecules and barium glass powder, making the surface of the material denser, reducing the coefficient of friction, and greatly enhancing wear resistance; nano-silica improves optical properties: the particle size of nanoparticles is smaller than the wavelength of visible light (400-800nm), reducing light scattering and improving the transparency and aesthetic effect of the material.
[0052] In this application, submicron-sized barium glass powder can reduce polymerization shrinkage: resin materials have a large shrinkage rate during the curing process, and the addition of a large amount of filler can effectively reduce shrinkage and reduce local stress, while improving the rigidity, strength, thermal stability and reducing water absorption of the product; submicron-sized barium glass powder can provide X-ray radiopaqueness: barium has the ability to block X-rays, which makes the restoration clearly distinguishable from natural tooth tissue on X-ray films, facilitating subsequent diagnosis and examination by dentists.
[0053] In some embodiments, the mass ratio of the barium silanized glass powder to the modified fumed silica is (10-20):1 (exemplary mass ratios are 10:1, 12:1, 15:1, 18:1, 20:1, etc.).
[0054] In some embodiments, the average particle size of the barium silanide glass powder is 0.7-1 μm (exemplary, the average particle size is 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, etc.).
[0055] In some embodiments, the average particle size of the modified fumed silica is 5-20 nm (exemplary average particle sizes are 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 17 nm, 20 nm, etc.).
[0056] In this application, when the mass ratio of barium silanide glass powder to modified fumed silica is within a defined range, and the average particle size of both is within a defined range, the two particles will have a stacking complementary effect in structure. When the average particle size of modified fumed silica is less than 5 nm, the surface area is too large and it is easy to agglomerate and not easy to disperse. If the average particle size of modified fumed silica exceeds 20 nm, the difference in particle size will affect the combination effect of the two and will not achieve the expected complementary effect.
[0057] In some embodiments, the preparation method of the filler includes: adding the modified solution to barium glass powder and fumed silica, ultrasonically dispersing at 50-70°C (exemplary temperatures are 50°C, 55°C, 60°C, 65°C, 70°C, etc.) for 30-60 min (exemplary ultrasonic dispersion times are 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.), and drying for 10-14 h to obtain the filler.
[0058] In some embodiments, the mass ratio of the modified solution to barium glass powder is (1.5-5):1 (exemplary mass ratios include 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, etc.).
[0059] In some embodiments, the mass ratio of the modified solution to fumed silica is (0.5-3.5):1 (exemplary mass ratios include 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, etc.).
[0060] In some embodiments, the drying process includes: first drying at 55-65°C (exemplary, temperatures are 55°C, 58°C, 60°C, 62°C, 65°C, etc.) for 1-3 hours (exemplary, time is 1 hour, 2 hours, 3 hours, etc.), then drying at 70-80°C (exemplary, temperatures are 70°C, 72°C, 75°C, 78°C, 80°C, etc.) for 1-3 hours (exemplary, time is 1 hour, 2 hours, 3 hours, etc.), and then drying at 85-95°C (exemplary, temperatures are 85°C, 88°C, 90°C, 92°C, 95°C, etc.) for 7-9 hours (exemplary, time is 7 hours, 8 hours, 9 hours, etc.).
[0061] In some embodiments, the method for preparing the modified solution includes: mixing ethanol, water and a silane coupling agent to obtain a modified solvent.
[0062] In some embodiments, the mass ratio of ethanol, water and silane coupling agent is (5-8.5):(2-5.5):(0.5-1.5) (exemplary mass ratios are 5:2:0.5, 6:3:0.8, 7:4:1, 8:5:1.2, 8.5:5.5:1.5, etc.).
[0063] In some embodiments, the mixing rate is 400-600 rpm (exemplary rates are 400 rpm, 420 rpm, 450 rpm, 480 rpm, 500 rpm, 520 rpm, 550 rpm, 580 rpm, 600 rpm, etc.), and the mixing time is 0.5-2 h (exemplary times are 0.5 h, 1 h, 1.5 h, 2 h, etc.).
[0064] In some embodiments, the functional additives include any one or a combination of at least two of antioxidants, bactericides, emulsifiers, or pigments.
[0065] In some embodiments, the antioxidant includes any one or a combination of at least two of antioxidant 1010, antioxidant 1076, antioxidant 264 or antioxidant 168.
[0066] In some embodiments, the bactericide includes nano-silver.
[0067] In some embodiments, the emulsifier includes any one or a combination of at least two of octylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether, or higher carbon fatty alcohol polyoxyethylene ether.
[0068] In some embodiments, the pigment includes any one or a combination of at least two of iron oxide red, iron oxide yellow, or iron oxide black.
[0069] In some embodiments, this application provides a method for preparing a composite resin disk, the method comprising: (1) The resin matrix, filler and functional additives are mixed, dispersed and prepolymerized to obtain a mixture; (2) Degas the mixture obtained in step (1) and then mold and cure it to obtain a composite resin disc.
[0070] In this application, the composite resin disk (the structure of the composite resin disk is as follows) Figure 1 As shown, the preparation method of (with a diameter of 98.5 mm and a height of 14 mm) is simple, the process conditions are relatively mild, and it is easy to carry out large-scale production and application.
[0071] In some embodiments, the mixing and dispersion in step (1) includes a three-stage dispersion, wherein the first stage is premixing for 60-120 min (exemplary, the stirring speed is 2000-3000 rpm, 2200 rpm, 2500 rpm, 2800 rpm, 3000 rpm, etc.) at a temperature of 45-55℃ (exemplary, the temperature is 45℃, 48℃, 50℃, 52℃, 55℃, etc.) and a stirring speed of 2000-3000 rpm (exemplary, the stirring speed is 2000 rpm, 2200 rpm, 2500 rpm, 2800 rpm, 3000 rpm, etc.); the second stage is premixing for 55-65℃ (exemplary, the temperature is 55℃, 58℃, 60℃, 62℃, 65℃, etc.) and a stirring speed of 4000-6000 rpm (exemplary, the stirring speed is 4000 rpm, 4500 rpm, 5000 rpm, 5500 rpm, etc.). The first stage involves high-shear mixing at a frequency of 30-50 kHz (e.g., 30 kHz, 35 kHz, 40 kHz, 45 kHz, 50 kHz, etc.) and a stirring rate of 1000-2000 rpm (e.g., 1000 rpm, 1200 rpm, 1500 rpm, 1700 rpm, 2000 rpm, etc.) for 10-20 minutes (e.g., 10 minutes, 12 minutes, 15 minutes, 18 minutes, 20 minutes, etc.).
[0072] In some embodiments, the prepolymerization in step (1) includes a three-stage gradient heating, wherein: the temperature of the first stage is 50-70°C (exemplary, the temperature is 50°C, 55°C, 60°C, 65°C, 70°C, etc.), held for 20-40 min (exemplary, the time is 20 min, 25 min, 30 min, 35 min, 40 min, etc.); the temperature of the second stage is 80-100°C (exemplary, the temperature is 80°C, 85°C, 90°C, 95°C, 100°C, etc.), held for 10-30 min (exemplary, the time is 10 min, 15 min, 20 min, 25 min, 30 min, etc.); and the temperature of the third stage is 110-130°C (exemplary, the temperature is 110°C, 115°C, 120°C, 125°C, 130°C, etc.), held for 5-15 min (exemplary, the time is 5 min, 8 min, 10 min, 12 min, 15 min, etc.).
[0073] In some embodiments, the prepolymerization in step (1) is carried out under stirring conditions, wherein the stirring rate is 200-1000 r / min (exemplary rates are 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min, etc.).
[0074] In some embodiments, the pressure of molding and curing in step (2) is 100-300 MPa (exemplary pressures include 100 MPa, 120 MPa, 150 MPa, 180 MPa, 200 MPa, 220 MPa, 250 MPa, 280 MPa, 300 MPa, etc.).
[0075] In some embodiments, the molding curing in step (2) includes first curing at 110-180℃ (exemplary, temperatures are 110℃, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, etc.) for 1-3 hours (exemplary, time is 1 hour, 2 hours, 3 hours, etc.), and then curing at 70-80℃ (exemplary, temperatures are 70℃, 72℃, 75℃, 78℃, 80℃, etc.) for 8-12 hours (exemplary, time is 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc.).
[0076] In some embodiments, the degassing in step (2) is accomplished using a vacuum device combined with instantaneous pressure relief technology.
[0077] In some embodiments, the vacuum device is as follows Figure 2 As shown, it includes: a vacuum pump, a buffer tank, a vacuum chamber, and valves and fittings. It should be noted that the vacuum device is acquired through purchase; this application does not limit the specific structure and connection relationships, and those skilled in the art can purchase or customize it according to actual needs.
[0078] In this application, the volume of the buffer tank is 2m³. 3 The volume of the vacuum chamber is 0.025m. 3 The volume of the material is utilized, and by taking advantage of the high volume ratio between the buffer tank and the vacuum chamber, the vacuum chamber can be instantly brought to a vacuum level below -0.1 MPa. Before degassing, the valve between the buffer tank and the vacuum chamber is closed, and then the pressure inside the buffer tank is evacuated to below -0.1 MPa, while keeping the vacuum pump running to ensure continuous negative pressure. The material to be degassed is placed into the vacuum chamber, and then the valve between the buffer tank and the vacuum chamber is quickly opened, maintaining degassing at -0.1 MPa for 5-10 minutes.
[0079] In this application, the advantages of using a vacuum device combined with instantaneous pressure relief technology are as follows: Typically, degassing devices use a vacuum pump directly connected to a vacuum chamber, continuously drawing in air until reaching -0.1 MPa. This process is relatively slow, and the high resistance to the rise of bubbles in high-viscosity liquids causes a small number of micro- and nano-bubbles to adhere to the container wall or liquid surface during their ascent, making complete removal difficult. This device utilizes the large-capacity negative pressure space provided by the buffer tank as a buffer, compensating for the time difference in the vacuum pump's suction process. Reaching -0.1 MPa instantaneously upon opening the valve, the gas inertia causes large bubbles to rise rapidly to the liquid surface and burst. This rapid bursting of large bubbles simultaneously drives the rise and bursting of micro- and nano-bubbles, completing the complete degassing of the solution.
[0080] In some embodiments, the composite resin disc is used for denture restoration.
[0081] The following section will conduct performance tests on the raw materials or manufacturing methods of the composite resin discs provided in the embodiments of this application, as well as related comparative examples.
[0082]
Preparation Example 1
[0083] A3. Add 50 g of the modified solution to 15 g of fumed silica, ultrasonically disperse at 60°C for 45 min, dry at 60°C for 2 h, dry at 75°C for 2 h, and then dry at 90°C for 8 h to obtain silanized modified fumed silica.
[0084] Tests revealed that the average particle size of the obtained barium silanized glass powder was 0.7-1 μm, and the average particle size of the modified fumed silica was 5-20 nm.
[0085]
Example 1
[0086] This embodiment also provides a method for preparing a composite resin disk, including: (1) The above raw materials are mixed and dispersed in three stages. The first stage is premixed for 90 min at a temperature of 50℃ and a stirring rate of 2500 rpm. The second stage is high-shear mixing for 60 min at a temperature of 60℃ and a stirring rate of 5000 rpm. The third stage is ultrasonic mixing for 15 min at a frequency of 40 kHz and a stirring rate of 1500 rpm. Then, the prepolymerization is carried out in three steps at a stirring rate of 500 r / min. The first step is to heat to 60℃ and hold for 30 min. The second step is to heat to 90℃ and hold for 20 min. The third step is to heat to 120℃ and hold for 10 min to obtain the mixture. (2) The mixture obtained in step (1) was degassed by a vacuum device at -0.1 MPa combined with instantaneous depressurization technology. Then, it was cured at 130°C for 2 hours under a pressure of 200 MPa, and then cured at 75°C for 10 hours to obtain a composite resin disc.
[0087] Examples 2-7 and Comparative Examples 1-3 provide a composite resin disk and process parameters, as shown in Table 1:
[0088] Table 1
[0089] The mixtures obtained in step (1) of Examples 1-7 and Comparative Examples 1-3 were subjected to flexural strength and Vickers hardness tests. The test standard for flexural strength was YY / T 0710 2009 / ISO 10477 2004, and the test standard for Vickers hardness was GB / T 4340.1-2024 Vickers hardness. The test results are shown in Table 2.
[0090] Table 2
[0091] A comparison of Examples 1-7 and Comparative Examples 1-3 shows that the composite resin discs prepared using the raw materials of this application have good flexural strength and Vickers hardness.
[0092] It should be noted that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential," etc., are used only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on this application. The directional terms "inner" and "outer" refer to the inside or outside relative to the outline of the component itself. For example, if a device in the drawings is inverted, a device described as "above" or "on top of" other devices or structures will subsequently be positioned as "below" or "under" other devices or structures. Thus, the exemplary term "above" can include both "above" and "below." The device may also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatial relative descriptions used herein are interpreted accordingly.
[0093] It should also be noted that the terms "one embodiment," "another embodiment," and "embodiment" used in this application refer to specific features, structures, or characteristics described in connection with that embodiment, which are included in at least one embodiment described in the general description of this application. The appearance of the same expression in multiple places in the specification does not necessarily refer to the same embodiment. Furthermore, when a specific feature, structure, or characteristic is described in connection with any embodiment, the intention is to suggest that implementing such a feature, structure, or characteristic in conjunction with other embodiments also falls within the scope of this application.
[0094] In the above embodiments, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.
[0095] It should also be noted that the above are merely preferred embodiments of this application and do not limit the scope of patent protection of this application. Any equivalent structural or procedural changes made using the content of this application’s specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of this application.
Claims
1. A composite resin disc, characterized in that, The raw materials for the composite resin disc include: 10-30% resin matrix, 70-90% filler, and the balance functional additives by weight. The filler is a combination of barium silanide glass powder and modified fumed silica; The resin matrix comprises 5-10% by weight of bisphenol A-glycidyl methacrylate, 2-10% of urethane dimethacrylate, 1-10% of triethylene dimethacrylate, 0.1-1% of hydroxyethyl methacrylate, 0.1-1% of methyl methacrylate, and 0.1-1% of methacrylic acid.
2. The composite resin disc according to claim 1, characterized in that, The mass ratio of the barium silanide glass powder to the modified fumed silica is (10-20):1; The average particle size of the barium silane glass powder is 0.7-1 μm; The modified fumed silica has an average particle size of 5-20 nm.
3. The composite resin disc according to claim 1, characterized in that, The method for preparing the filler includes: The modified solution was added to barium glass powder and fumed silica, ultrasonically dispersed at 50-70℃ for 30-60 min, and dried to obtain the filler. The mass ratio of the modified solution to barium glass powder is (1.5-5):1; The mass ratio of the modified solution to fumed silica is (0.5-3.5):1; The drying process includes: first drying at 55-65℃ for 1-3 hours, then drying at 70-80℃ for 1-3 hours, and finally drying at 85-95℃ for 7-9 hours. The method for preparing the modified solution includes: mixing ethanol, water and a silane coupling agent to obtain the modified solution; The mass ratio of the ethanol, water, and silane coupling agent is (5-8.5):(2-5.5):(0.5-1.5); The mixing rate is 400-600 rpm, and the mixing time is 0.5-2 h.
4. The composite resin disk according to claim 1, characterized in that, The functional additives include any one or a combination of at least two of antioxidants, bactericides, initiators, emulsifiers, or pigments; The antioxidant includes any one or a combination of at least two of antioxidants 1010, 1076, 264 or 168; The bactericide includes nano-silver; The initiator includes benzoyl peroxide; The emulsifier includes any one or a combination of at least two of octylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether, or higher carbon fatty alcohol polyoxyethylene ether. The pigments include any one or a combination of at least two of iron oxide red, iron oxide yellow, or iron oxide black.
5. The composite resin disk according to claim 1, characterized in that, The flexural strength of the composite resin disk is 300-350 MPa; The elastic modulus of the composite disk is 14-20 GPa; The Vickers hardness of the composite disk is 75-85 HV0.2; The polymerization shrinkage rate of the composite disk is 0.
6. The method for preparing the composite resin disk according to any one of claims 1-5, characterized in that, The preparation method includes: (1) The resin matrix, filler and functional additives are mixed, dispersed and prepolymerized to obtain a mixture; (2) Degas the mixture obtained in step (1) and then mold and cure it to obtain a composite resin disc.
7. The preparation method according to claim 6, characterized in that, The mixing and dispersion in step (1) includes three-stage dispersion. The first stage is premixing for 60-120 min at a temperature of 45-55℃ and a stirring rate of 2000-3000 rpm. The second stage is high-shear mixing for 30-90 min at a temperature of 55-65℃ and a stirring rate of 4000-6000 rpm. The third stage is ultrasonic mixing for 10-20 min at a frequency of 30-50 kHz and a stirring rate of 1000-2000 rpm. The prepolymerization in step (1) includes a three-stage gradient heating, wherein: the temperature of the first stage is 50-70℃ and held for 20-40 min; the temperature of the second stage is 80-100℃ and held for 10-30 min; and the temperature of the third stage is 110-130℃ and held for 5-15 min.
8. The preparation method according to claim 6, characterized in that, The degassing in step (2) is completed using a vacuum device combined with instantaneous pressure relief technology.
9. The preparation method according to claim 6, characterized in that, The pressure for molding and curing in step (2) is 100-300 MPa; Step (2) involves curing at 110-180℃ for 1-3 hours, followed by curing at 70-80℃ for 8-12 hours.
10. The application of the composite resin disc according to any one of claims 1-5 in denture restoration.
